SURG-20. CRANIOTOMY AND SURVIVAL FOR PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA. Issue 11 (6th November 2017) - Rae, Ali; Mehta, Amol; Cloney, Michael; Kinslow, Connor; Wang, Tony; Bhagat, Govind; Canoll, Peter; Zanazzi, George; Sisti, Michael; Sheth, Sameer; Connolly, E Sander; McKhann, Guy; et al.
Abstract: PURPOSE: Cytoreductive surgery is considered controversial and high-risk for primary central nervous system lymphoma (PCNSL). We investigated survival following craniotomy or biopsy for PCNSL. METHODS: The National Cancer Database-Participant User File (NCDB, n=8, 936), Surveillance, Epidemiology, and End Results Program (SEER, n=5, 615), and an institutional series (IS, n=132) were used. We investigated the relationship among craniotomy, prognostic factors, and survival for PCNSL. RESULTS: In NCDB, craniotomy was associated with increased median survival over biopsy (19.5 vs. 11.0 months), independent of subsequent radiation and chemotherapy (HR 0.83, p<0.001). We found a similar trend with survival for craniotomy vs. biopsy in the IS (HR 0.68, p = 0.15). In SEER, gross total resection (GTR) was associated with increased median survival over biopsy (29 vs. 10 months, HR 0.68, p<0.001). The survival benefit associated with craniotomy was greater within Recursive Partitioning Analysis (RPA) class 1 group in NCDB (95.1 v. 29.1 months, HR 0.66, p<0.001), but was smaller for RPA 2-3 (14.9 vs. 10.0 months, HR 0.86, p<0.001). A surgical risk category (RC) considering lesion location and number, age, and frailty was developed. Craniotomy was associated with increased survival versus biopsy for patients with low-RC (133.4 vs. 41.0 months, HR 0.33, p=0.01), but not high-RC in the IS. CONCLUSION: Craniotomy is associated with increased survival over biopsy for PCNSL in three datasets. Prospective studies are necessary to adequately evaluate this relationship. Such studies should focus on patients most likely to benefit from cytoreductive surgery; i.e. those with favorable RPA and RC.